2023
DOI: 10.3390/pharmaceutics15020478
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological, Molecular, and Histopathological Investigation of the Potential Activity of Propolis and Wheat Germ Oil against Acute Toxoplasmosis in Mice

Abstract: Toxoplasmosis is one of the most common parasitic zoonoses that affects all vertebrates. The drugs most commonly used against toxoplasmosis have many side effects, making the development of new antiparasitic drugs a big challenge. The present study evaluated the therapeutic effectiveness of novel herbal treatments, including propolis and wheat germ oil (WGO), against acute toxoplasmosis. A total of 50 albino mice were divided into five groups: group 1 (G1) (non-infected and non-treated); group 2 (G2) (infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The work revealed the potential synergistic effects of propolis and WGO on an herbal substance that could be considered an effective treatment of acute toxoplasmosis infection. These herbal substances reduced the parasite load significantly [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work revealed the potential synergistic effects of propolis and WGO on an herbal substance that could be considered an effective treatment of acute toxoplasmosis infection. These herbal substances reduced the parasite load significantly [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the previous investigations, we found the presence of some other secondary metabolites, such as glycosides, tannins, and terpenoids, was also confirmed in this extract [ 9 , 10 ]. Barakat et al (2023) stated that propolis has many plant secondary metabolite contents (phenolic compounds) that work against many extracellular and intracellular protozoan parasites [ 33 ]. Reviews have demonstrated the antifungal, antiviral, antibacterial, and antiparasitic effects of flavonoids and phenolic compounds [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in many in vitro and in vivo studies for its ability to reduce the oxidative stress, improve the lipid metabolism, enhance the fertility, and inhibit the carcinogenesis (25,26,(28)(29)(30). Owing to the active ingredients of both propolis and WGO, they are commonly used as herbal therapies in many diseased conditions, including chronic toxoplasmosis (31)(32)(33)(34). However, their potential protective effect against acute toxoplasmosis is not clear yet.…”
Section: Introductionmentioning
confidence: 99%